Advances and challenges of the racial quota system in brazilian and federal public institutions of higher education and dentistry: a narrative review - Guimarães , Camila Souza; de Almeida , Luiz Eduardo; de Oliveira, Valéria (Seven Editora, 2023)
This is a narrative review, whose objective was to analyze the effectiveness (advances and challenges) of the racial quota system in federal and Brazilian public institutions of higher education, and to suggest the need for further reflection on the significance of the theme in courses dentistry specifically. Through a systematic search and applying the eligibility criteria, 15 articles were considered eligible. Of the results, it is highlighted that, respectively, 73% (11 articles), 6.6% (01 article), 6.6% (01 article) and 12% (02 articles) have as their central theme Education, Sciences Social, linguistics and the field of human sciences. The conclusion of this work is that, since the regulation of Law No. 12,711, accessibility to Brazilian public and higher education by students targeted by this law is a major advance. However, it appears that, despite the evidenced prosperity, there are still limitations that interfere with the range of benefits arising from this policy. In this way, its continued improvement becomes essential in order to minimize its limitations, until then, perceived in its practice. DOI: https://doi.org/10.56238/devopinterscie-035